Defining business education and supporting wholesale marketing for beginning specialty crop farmers - McManus, Megan C. (Kansas State University, 2021)
Despite their contribution to the production of fresh fruits and vegetables for local consumers, beginning and small-scale specialty crop growers face significant challenges to maintain their economic sustainability, including maintaining a sufficient level of income. In 2017, approximately 60% of all Kansas and Missouri specialty crop operations had a gross revenue of less than $10,000, and a recent study suggested that curricula related to business skills for beginning specialty crop growers in the region are lacking. The overall goal of this thesis was to address these challenges by: (i) identifying farm business skills that are fundamental for successful and beginning specialty crop growers and (ii) providing resources that growers can use to scale-up their marketing efforts. There is little information currently available on what kind of education and/or training beginning specialty crop farmers need to possess the business skills that can make their operation profitable. A study was conducted using synchronous and asynchronous methods to define and prioritize the business skills that specialty crop growers in Kansas and Missouri view as necessary to be profitable. Online survey (n=106) results suggested that farmers place high emphasis on all standard business education curricula, however, perception of resources surrounding these skills were mostly neutral to unsatisfied. Responses differed among farmers, indicating years of experience, employment and ownership can impact the perception of skill importance and satisfaction of resources. A series of asynchronous and synchronous online focus groups (n=24) revealed themes on business skills, obstacles to profitability, resources, and desired courses surrounding business education. These findings can help provide educators a better idea of what small-scale specialty crop farmers need for business education. Based on our results, curricula developed from this data should promote farmer business literacy and ultimately improve farm business viability. One of the primary areas that was an identified area of need was related to marketing for beginning farmers. A manual was developed to help beginning specialty crop growers increase gross revenue, “Demystifying the Wholesale Market”, to outline marketing opportunities and/or best management practices for beginning farmers that are looking to enter the wholesale market in the Kansas City region. As American agriculture continues to evolve with changing market demands and resource availability, the economic sustainability of small-scale growers is critical to a thriving local food system.
Keywords: Beginning farmers; Agricultural education; Specialty crops; University extension; Farm business